Staroobrjadcy Južnoj Ameriki očerki istorii, kulʹtury, jazyka - Rovnova, Olʹga Gennadʹevna 1960-2022 (Studia Philologica, 2022)
"The monograph presents some results of studying the history, culture and Russian dialect language of the Old Believers living in Argentina, Bolivia, Brazil, Uruguay. The research was started in 2006 at the Vinogradov Russian Language Institute of RAS on the initiative of the author. The main attention is paid to various aspects of the Russian dialect language of the Old Believers. The monograph includes a fragment of the future "Dictionary of the dialect of the Old Believers of South America". The book is addressed to specialists in the field of Old Believers and readers interested in the history of Russia and the Russian language."